Dishonest behaviour in ambiguous tasks: The interplay between effort and competence - Michael Puntiroli; Serhiy Kandul; Valéry Bezençon; Bruno Lanz (University of Neuchâtel, Institute of Economic Research (IRENE), 2023)
Ambiguous tasks present information that is subject to varying interpretations. Extensive research suggests that ambiguous tasks may lead to dishonest behaviour in various contexts (e.g. claiming back expenses or setting project deadlines), because individuals interpret the information in self-serving ways. Despite "effort" and "competence" potentially helping to disambiguate tasks, and thus deter dishonest behaviour, no research to date has investigated their role in this context. This paper presents a novel experimental design investigating dishonest behaviour in settings involving ambiguous tasks. We explore how both the effort required to disambiguate a task and individual competence impact dishonest behaviour. In Study 1, participants resolved an ambiguous task and self-reported their performance, validating that ambiguity and dishonesty increase in unison. Study 2 further demonstrated that participants who exerted more effort to disambiguate information were more successful at completing the task, leading to less dishonesty. Lastly, in Study 3, we increased participants' competence in resolving ambiguity through a brief training session, which effectively reduced the effort required to disambiguate the task, leading to a subsequent decrease in dishonest behaviour. Overall, our results suggest that dishonesty can be mitigated by either encouraging individuals to invest effort into disambiguating information or by enhancing their competence at solving ambiguous tasks through training sessions.
Keywords: 330; ambiguity; competence; effort; training; dishonesty